Does Public Expenditure on Education Cause Economic growth in Nepal? - Dhakal, Narayan Prasad; Khanal, Santosh (Devkota Journal of Interdisciplinary Studies, 2024)
The only way to boost economic growth, every country in the world agreed, was to improve education. The purpose of this study was to investigate the potential relationship between economic growth and public education spending. This was achieved by using time series data from 1988 to 2022 in conjunction with the ARDL model. The study investigated the impact of a variety of factors on GDP growth in order to ascertain the significance of this correlation. The number of secondary schools, the duration of a student's school year, the proportion of students who passed the SEE, government spending on education, and gross fixed capital formation are a few variables that can be altered. Additionally, this investigation investigated several other critical variables that impact economic expansion. The findings support past research and demonstrate a connection between public education spending and economic growth. Study findings indicate that increased funding for education is boosting the national economy. Analysis also highlights the role that gross fixed capital formation plays in the process of economic expansion. The exceptionally strong negative sign of the error correction term suggests a strong long-term correlation between the variables. The heteroscedasticity, normality, and Breusch-Godfrey LM tests generate P-values exceeding 5%, as expected. This model is devoid of heteroscedasticity and autocorrelation. The government should allocate a substantial portion of its budget to the education sector and prioritize funding. The study suggests that additional indicators should be investigated in order to support the idea that education is the foundation of any economy.